Deoxyuridine triphosphatase expression defines the transition from dormant to sprouting potato tuber buds - Senning, Melanie; Sonnewald, Uwe; Sonnewald, Sophia (Molecular Breeding, 2010)
Identification of molecular markers defining the end of tuber dormancy prior to visible sprouting is of agronomic interest for potato growers and the potato processing industry. In potato tubers, breakage of dormancy is associated with the reactivation of meristem function. In dormant meristems, cells are arrested in the G(1)/G(0) phase of the cell cycle and re-entry into the G(1) phase followed by DNA replication during the S phase enables bud outgrowth. Deoxyuridine triphosphatase (dUTPase) is essential for DNA replication and was therefore tested as a potential marker for meristem reactivation in tuber buds. The corresponding cDNA clone was isolated from potato by PCR. The deduced amino acid sequence showed 94% similarity to the tomato homologue. By employing different potato cultivars, a positive correlation between dUTPase expression and onset of tuber sprouting could be confirmed. Moreover, gene expression analysis of tuber buds during storage time revealed an up-regulation of the dUTPase 1 week before visible sprouting occurred. Further analysis using an in vitro sprout assay supported the assumption that dUTPase is a good molecular marker to define the transition from dormant to active potato tuber meristems.
Keywords: Solanum tuberosum; Potato; Tuber dormancy; Tuber sprouting; Meristem reactivation; DNA replication; dUTPase